2009
DOI: 10.1159/000205580
|View full text |Cite
|
Sign up to set email alerts
|

Association Analysis of Brain-Derived Neurotrophic Factor Gene Polymorphisms in Asthmatic Families

Abstract: Background: A role for neuronal modulation of inflammation and airway hyper-responsiveness has been well described in asthma, and neurotrophins provide the link between inflammation and neuronal dysfunction. Brain-derived neurotrophic factor (BDNF) is an important mediator in this interaction. The aim of this study was to analyze the possible relationship between polymorphisms of the gene encoding BDNF and susceptibility to asthma. Methods: 341 families with at least 2 siblings with asthma were genotyped for 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 68 publications
3
10
1
Order By: Relevance
“…Previous studies investigating the impact of genetic variation in BDNF have shown conflicting results [7,11,12]. Negative association results presented here for 3 BDNF polymorphisms (rs12273363, rs7124442, rs6265) are consistent with those obtained in a German cohort[11] and also with data published for a large British cohort of asthmatic siblings [12].…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies investigating the impact of genetic variation in BDNF have shown conflicting results [7,11,12]. Negative association results presented here for 3 BDNF polymorphisms (rs12273363, rs7124442, rs6265) are consistent with those obtained in a German cohort[11] and also with data published for a large British cohort of asthmatic siblings [12].…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have investigated the association of the rs7124442 SNP to eating disorders, cognitive abilities in the elderly, major depression, susceptibility to asthma, Parkinson's disease, autism, Alzheimer's disease and migraine [67], [68], [69], [70], [71], [72], [73]. The only significant associations identified were to eating disorders and high plasma BDNF levels [67] as well as a significant negative influence of TT genotype on treatment response to SSRI, opposed to CC [69].…”
Section: Discussionmentioning
confidence: 99%
“…With evidence for BDNF expression and signaling in airway innervation, epithelium and smooth muscle there is obviously significant interest in the potential role for targeting NTs such as BDNF in asthma (Abram et al, 2009; Bennedich Kahn et al, 2008; Dagnell et al, 2007; Freund-Michel and Frossard, 2008; Frossard et al, 2004; Nassenstein et al, 2006; Nockher and Renz, 2006; Prakash et al, 2009; Renz et al, 2004; Rochlitzer et al, 2006). In this regard, there is some evidence for an association between BDNF and asthma, particularly in children as well as increased asthma association with a variant of the BDNF gene (Andiappan et al, 2011; Koskela et al, 2010; Szczepankiewicz et al, 2007; Szczepankiewicz et al, 2010; Szczepankiewicz et al, 2009; Yinli et al, 2013; Zeilinger et al, 2009). Furthermore, in humans as well as in mouse models of asthma, allergen challenge increases NGF and BDNF levels in bronchoalveolar lavage fluid (Braun et al, 1999; Virchow et al, 1998).…”
Section: Bdnf and Asthmamentioning
confidence: 99%